2015 3rd International Conference on Artificial Intelligence, Modelling and Simulation (AIMS) 2015
DOI: 10.1109/aims.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Multi-model, Multi-level Artificial Neural Network for Eczema Skin Lesion Detection

Abstract: There are several current systems developed to identify common skin lesions such as eczema that utilize image processing and most of these apply feature extraction techniques and machine learning algorithms. These systems extract the features from pre-processed images and use them for identifying the skin lesions through machine learning as the core. This paper presents the design and evaluation of a system that implements a multi-model, multi-level system using the Artificial Neural Network (ANN) architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…To improve the accuracy of current research, contextual information could be added for consideration by AI programs. [ 4 23 ]…”
Section: Current Status Of Ai Application In Dermatologymentioning
confidence: 99%
“…To improve the accuracy of current research, contextual information could be added for consideration by AI programs. [ 4 23 ]…”
Section: Current Status Of Ai Application In Dermatologymentioning
confidence: 99%
“…This is a notable limitation considering that the incidence of scalp psoriasis is 45-56% and nail psoriasis is 23-27% among psoriatic patients [57]. CNNs have been created for other diseases, such as atopic dermatitis [58], onychomycosis [56], and rosacea [59]. To classify onychomycosis, Han et al [56] used a R-CNN to generate a training datasets of 49,567 images of nails and found that a combination of their datasets performed better than dermatologists.…”
Section: Other Dermatological Diseasesmentioning
confidence: 99%
“…105 Automated diagnosis of other erythemato-squamous diseases such as seborrheic dermatitis, atopic dermatitis, lichen planus, pityriasis rosea and pityriasis rubra pilaris has been studied using various clinical and histopathological features. 106,107 Acne New technologies in imaging and software solutions have been developed in acne and rosacea evaluation. A study by Min et al showed that compared with manual counting performed by an expert dermatologist, the sensitivity and positive predictive value of the lesion-counting program was greater than 70% for papules, nodules, pustules, and whitehead comedones.…”
Section: Psoriasismentioning
confidence: 99%